2001
DOI: 10.1359/jbmr.2001.16.4.605
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Immunoradiometric Assay Exclusively for Biologically Active Whole Parathyroid Hormone 1–84: Implications for Improvement of Accurate Assessment of Parathyroid Function

Abstract: We developed a novel immunoradiometric assay (IRMA; whole parathyroid hormone [PTH] IRMA) for PTH, which specifically measures biologically active whole PTH(1-84). The assay is based on a solid phase coated with anti-PTH(39-84) antibody, a tracer of 125 I-labeled antibody with a unique specificity to the first N-terminal amino acid of PTH(1-84), and calibrators of diluted synthetic PTH(1-84). In contrast to the Nichols intact PTH IRMA, this new assay does not detect PTH(7-84) fragments and only detects one imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
266
2
19

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(298 citation statements)
references
References 27 publications
11
266
2
19
Order By: Relevance
“…Aligned with findings by other authors, we found a high correlation between the two methods in these patients (23)(24)(25). However, the Passing-Bablok and BlandAltman tests showed a proportional and systematic difference between both methods, indicating that the second and third-generation PTH assays may not be used interchangeably.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Aligned with findings by other authors, we found a high correlation between the two methods in these patients (23)(24)(25). However, the Passing-Bablok and BlandAltman tests showed a proportional and systematic difference between both methods, indicating that the second and third-generation PTH assays may not be used interchangeably.…”
Section: Discussionsupporting
confidence: 84%
“…In the literature, there are only a few studies evaluating third-generation PTH assays in patients with primary hyperparathyroidism (8,(23)(24)(25). Silverberg and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Serum parathyroid hormone (PTH) was measured by a chemiluminescent method (Corning-Nichols Laboratory, San Juan Capistrano, CA, USA) that detects both a large, terminally truncated (7-84) fragment of PTH and the intact 1-84 molecule [23]. Intra-assay and inter-assay variabilities are 3.4% and 5.6%, respectively.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…75 It has been suggested that this discrepancy may be related to the presence of a truncated PTH molecule which is recognized by the standard two-site immunoassays. 76,77 If this circulating PTH fragment were to act as an inhibitor of PTH bioactivity it might explain the previous studies on pseudohypoparathyroidism. Further developments are awaited with interest.…”
Section: Last But By No Means Leastmentioning
confidence: 99%